Psychoeducation of Positive Parenting for Mothers with Middle-to-low Socioeconomic Status - Mahardhika Annisa Tuzzuhro; Puji Lestari Suharso; Efriyani Djuwita (Jurnal Ilmiah Psikologi MIND SET, 2021)
Mothers in middle-to-low socioeconomic status tend to treat children with harsh punishment and presume it as an effective way, it indicates lack of comprehension about positive parenting, which may hinder child optimal development, especially in critical age 3 to 5 years old. Psychoeducation is one of interventions which is needed to improve comprehension of positive parenting for 3 to 5 years old children. This study aims to find the effectiveness of psychoeducation in improving comprehension of positive parenting for mothers of 3 to 5 years old children with middle-to-low socioeconomic status. Design of this study is one group pretest-posttest design. The subjects are 14 mothers with middle-to-low socioeconomic status background. The psychoeducation was held for three days continuously through video conference. The data were collected 3 times, before and immediately after the intervention, and 10 days after the intervention. Data analysis using Wilcoxon Signed-Rank Test shows significant score difference between before and after psychoeducation (p<0.05). It shows increasing score of positive parenting comprehension after attending the psychoeducation. However, the score decreased in 10 days after the intervention. The study resulted that psychoeducation required a break. Next research, sessions in psychoeducation can be done interspersed not continuously.